Minimally invasive coronary artery bypass (MICS CABG) in Bosnia and Herzegovina: a single centre, single surgeon cohort experience - Nermir Granov; Armin Šljivo; Ermina Mujičić; Damir Rebić; Alen Džubur; Edin Begić; Tarik Selimović; Zlatan Zvizdić; Almir Fajkić; Asmir Jonuzi; Edin Kabil; Slavenka Štraus (Medicinski glasnik, 2023)
Aim: This is the first research in Bosnia and Herzegovina presenting minimally invasive coronary artery bypass grafting surgery (MICS CABG) experience, advantages, and outcomes as compared to conventional surgery (OPEN CABG). Methods: This retrospective cross-sectional study was conducted between January 2019 and November 2022 and included patients with indication for surgical revascularization. Results: Among 237 patients, males predominated, 182 (76.7%), with a mean body mass index (BMI) of 28.4±3.9, median The Society of Thoracic Surgery Risk (STS) score of 1.55 (0.8, 4.0), short term STS score of 11.2 (6.8, 23.7), mean age of 64.8±8.7 (ranging 41-83) years, 122 (51.4%) underwent OPEN CABG and 115 (48.6%) MICS CABG. MICS CABG took less time (p<0.001; OPEN 3.5±0.8h; MICS 2.8±0.8h) and needed less mechanical ventilation (p<0.001, OPEN 17.3±11.9h; MICS 13.0±12.5h) than OPEN CABG. Even though there was no difference in hospitalization length between groups (OPEN (7.5±3.2), MICS (7.1±4.0)), patients receiving MICS (2.9±1.5) spent less time in the ICU (p=0.0013) than OPEN CABG (3.6±2.8). OPEN CABG used also more blood derivatives, red blood cells (OPEN 292 vs MICS 55), plasma (OPEN 270 vs MICS 86) and platelets (OPEN 71 vs MICS 28). Conclusion: Patients undergoing MICS CABG in Bosnia and Herzegovina had less mechanical ventilation hours and less ICU duration compared to OPEN CABG even though the hospitalization duration was very similar. MICS CABG takes less time to be conducted, has fewer CPRs postoperatively, uses less blood derivatives including red blood cells, plasma and platelets.
Keywords: cardiovascular diseases; cardiac surgical procedures; coronary artery disease